Penanganan kasus abortus inkomplit pada puskesmas PONED di Kabupaten Sumbawa Barat - Kurniaty Kurniaty; Djaswadi Dasuki; Abdul Wahab (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Success rate in handling incomplete abortion in EmOC primary health care in West SumbawaPurposeThis study explored the success of incomplete abortion in EmOC PHC in West Sumbawa.MethodThis research used descriptive analytic design with mix method approach. Quantitative research with cross sectional design and qualitative research with multiple-case study approach. The quantitative research sample is mother with incomplete abortion and qualitative research sample that is midwife, doctor and head of Puskesmas. Quantitative data analysis used chi-square test and logistic regression. Qualitative data collection using indepth interview method.ResultsHandling of successful incomplete abortus was 63,3% and most of EmOC PHC was complete 67,3%. There is a significant correlation between the success of incomplete abortion handling with the completeness of EmOC PHC. The likelihood of successful completion of incomplete abortion cases in complete EmOC PHC was 4.1 times greater than that of incomplete EmOC PHC. There was a significant relationship between maternal gestational age at abortion with successful incomplete abortion treatment (OR = 7,1; CI95% 1.27-40,2). Qualitative results show that EmOC teamwork can influence the success of handling incomplete abortion cases.ConclusionCompleteness of EmOC PHC has relationship with handling of incomplete abortus case. Increased knowledge and competence of health workers in the handling of incomplete abortion, so that in case management is more prepared and competent.